Comparison between different methods in evaluating haemodialysis adequacy - Usprcov, Julijana; Pushevski, Vladimir; Shterjova Markovska, Zhaklina; Kabova, Angela; Milenkova, Mimoza; Trajcheska, Lada; Filipovski Stefan; Rambabova Bushljetic, Irena; Gjorgjievski, Nikola (Oxford University Press (OUP), 2025)
Background and Aims An increasing number of patients with chronic kidney disease (CKD) increased the need for hemodialysis. Inadequate hemodialysis affects morbidity and mortality of hemodialysis patients. KDOQI guidelines recommend that Kt/V should be kept above 1.2 or URR 65% for thrice weekly routine hemodialysis. The aim of this study was to compare the urea reduction ratio (URR), Kt/V estimation by Daugirdas formula with the results measured by an Online Clearance Monitor (OCM). Method Cross-sectional study was conducted on 15 patients on hemodiafiltration (HDF) with age 36–79 years, 4-hour hemodiafiltration sessions three times a week and hemodialysis experience ≥ 6 months, using highflux dialyzers. For every patient blood flow rate was ≥ 350 ml/min and dialysis flow rate was 500 ml/min. According to vascular access all had AVF. Kt/V was calculated by the OCM of the Nipro Surdial X machine (the hemodialysis machine automatically calculate the measured sodium ion clearance based on the plasma conductivity). Results A total of 80 sessions were assessed with a predominance of males 51% (8). The mean of URR was 78.4 ± 10. Mean Kt/V values obtained with the Daugirdas formula was 1.9 ± 0.19. Mean Kt/V delivered by machine (OCM) was 1.87 ± 0.2. There was no significant difference between age, sex, comorbidities with adequacy of hemodialysis. The study show that there was no significant difference between the URR and Kt/V calculated with the Daugirdas formula and the OCM in the evaluation adequacy of hemodialysis. Conclusion Online Clearance Monitor (OCM) can be used as noninvasive guide to the real-time adjustment of the dialysis dose.
Keywords: hemodialysiskidney failure; chronicdrug clearancecomorbidityhemodiafiltrationplasmaguidelinesmorbiditymortalitysodium ionsdialyzervascular accessunit of flow rateblood flow rateurea reduction ratio